Análisis descriptivo del Currículo de formación del docente de Matemáticas, frente al Currículo del Bachillerato General Unificado. - Buñay Quishpi, Lidia Margoth (2024)
The present work entitled Descriptive Analysis of the Mathematics teacher training curriculum, compared to the Unified General Baccalaureate Curriculum, was carried out to study the teacher training curriculum in the Pedagogy of Experimental Sciences Career: Mathematics and Physics in the area of Mathematics compared to the Unified General Baccalaureate curriculum, a quantitative approach has been used, with a non-experimental design, the type of research was descriptive, the number of Mathematics contents at the Unified General Baccalaureate level was considered. Of the Career observation was used as a technique and the observation sheet as a data collection instrument, it was found that there is 90.20% agreement and 9.80% nonagreement, where five subtopics are not addressed, from Block 1, two subtopics and from Block 2, three subtopics within the curriculum of the Pedagogy of Experimental Sciences Career: Mathematics and Physics. Finally, it is suggested to teachers that they work on a more detailed analysis of the topics and subtopics required in the Unified General Baccalaureate, which must be addressed in the degree, focusing on permanent updating.